Re-envisioning Technological Pedagogical Content Knowledge and Online Teaching Readiness of English for Foreign Language Pre-service Teachers in Language Teacher Education - Rafiq, Karmila Rafiqah M.; Yunus, Melor Md; Susiati, (Frontiers in Psychology, 2022)
The pandemic has brought online learning as the new norm in education, which invokes many issues, particularly in the quality of online education. The quality of teacher education is being questioned, particularly in imparting adequate Technological Pedagogical Content Knowledge (TPACK), which seems to be lacking in preparing teachers for sudden online learning. Though many studies were clustered around TPACK, there is still an unfilled gap in identifying whether the pre-service teachers are ready to teach online classes alongside their TPACK. Hence, this paper aims to determine 1) the level of TPACK and readiness and 2) the relationship between TPACK and readiness for English for Foreign Language (EFL) pre-service teachers in online learning during the pandemic. A survey was distributed to 197 EFL pre-service teachers with 35 items, in which the level of TPACK and readiness were analyzed descriptively with the mean score. The Pearson correlation examined the relationship between TPACK domains and readiness. The main findings showed that the level of TPACK and readiness of EFL pre-service teachers were high, particularly for Technological Knowledge (TK). However, the correlation results showed a weak positive correlation between TPACK domains and readiness. The highest correlation was between Technological Content Knowledge (TCK) and readiness, which is a new finding contributing to the body of knowledge. This paper implied that TPACK should also look into the online teaching readiness of pre-service teachers so that they are well equipped with the online pedagogical knowledge for effective teaching and learning.